Orbital lymphoblastic lymphoma in 7 years old child - Siwiec-Prościńska, Joanna; Gotz-Więckowska, Anna; Kocięcki, Jarosław (Klinika Oczna / Acta Ophthalmologica Polonica, 2012)
The aim of the study is to present a case of unilateral orbital tumor (lymphoma) in a 7 years old boy. The edema of the temporal area of the right orbit with considerable narrowing of the palpebral fissure increased quickly during about 3 weeks. The skin redness without increased skin warmness and hardening by palpation above the lesion were observed. The orbit ultrasound and nuclear magnetic resonance were performed and the biopsy for histopathologic evaluation and immunohistochemical staining was taken. The last examination reveled a very rare kind type of the lymphoma in this age and location – lymphoblastic lymphoma beginning from B cells. In case of lymphoma the biopsy for histopathologic and immunohistochemical evaluation is essential, allowing for diagnosis and appropriate chemotherapy, as far as there is different outline for the treatment of different lymphomas.